Thz polarizer using tunable metamaterials - Lo, Guo-Qing. (2013)
The polarization of electromagnetic (EM) wave plays an essential role in the application of optoelectronics, life science microscopy and photographic display[1]. The conversion of EM wave in one polarized direction to its orthogonal direction is usually quite weak in natural materials. This paper presents a tunable metamaterial which rotates the polarized direction up to 20° in THz regime. The metamaterial can be transformed to its non-superimposable mirror image and tunes the polarization angle, which can be applied as tunable wave plate and optical switch in THz regime.